Contaminacion bacteriana en la micropropagacion de raices y tuberculos tropicales en Cuba - Carrazana Garcia, D.=700 1 Folgueras Montiel, M.; Herrera Isla, M; Suarez Canino, N.; Rodriguez Rodriguez, J.A.; Del Sol, L.
(Es, En)
Ilus., 14 ref.
Keywords: XANTHOSOMA; COLOCASIA ESCULENTA; DIOSCOREA; MANIHOT ESCULENTA; IPOMOEA BATATAS; BACTERIA; CONTAMINACION BIOLOGICA; MICROPROPAGACION; RAICES; TUBERCULO; CUBA; MALANGA; ÑAME; YUCA; BONIATO